(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article sets the number and the list of personal names of newborn male in 1790-1795, describes common names from different chronological periods and analyzes their frequency of use, defines the statistical organization of male names, qualitative and quantitative changes of some names.